2018
DOI: 10.1089/pho.2018.4490
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Photobiomodulation for the Treatment of Major Depressive Disorder. The ELATED-2 Pilot Trial

Abstract: Objective: Our objective was to test the antidepressant effect of transcranial photobiomodulation (t-PBM) with near-infrared (NIR) light in subjects suffering from major depressive disorder (MDD). Background: t-PBM with NIR light is a new treatment for MDD. NIR light is absorbed by mitochondria; it boosts cerebral metabolism, promotes neuroplasticity, and modulates endogenous opioids, while decreasing inflammation and oxidative stress. Materials and methods: We conducted a double-blind, sham-controlled study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 59 publications
1
79
0
2
Order By: Relevance
“…Recruitment began in February 2014, and the study was completed in August 2015. The ELATED-2 clinical trial has already been described in detail [19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recruitment began in February 2014, and the study was completed in August 2015. The ELATED-2 clinical trial has already been described in detail [19].…”
Section: Methodsmentioning
confidence: 99%
“…Adult subjects (age 18-65 years) meeting the DSM-IV SCID criteria for MDD, with the degree of depression severity rated at least moderate (Hamilton Depression Rating Scale, HAM-D 17 total score ranging [14][15][16][17][18][19][20][21][22][23][24], were included in the study after providing written informed consent. During the current episode, subjects could have failed no more than one FDA-approved antidepressant medication (for at least 6 weeks) and no more than one course of structured psychotherapy for depression (for at least 8 weeks).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Отмечалось лишь одно достоверное (р < 0,05) различие: в группе ФХТ прирост баллов по модифицированной шкале Рэнкина составил в среднем 1,5 балла при контрольных значениях 1,1 балла. При этом наблюдался относительно больший прирост внимания в тесте Шульте (27,8 однако это различие не достигало уровня достоверного (р = 0,07). Данные, представленные в табл.…”
Section: результатыunclassified
“…15 A wide range of studies, in both animal models and humans, have shown that PBM causes minimal or no adverse effects while producing therapeutic effects. 10,16,17 Although MDD has a broad age of onset, 2,4 most previously published studies have focused on t-PBM treatments in only middle-aged adult brain models. 18 However, personalization of treatments is key to increasing success rate and tolerability; therefore our interest is in developing precise PBM treatment strategies adapted for individual patients.…”
Section: Introductionmentioning
confidence: 99%